Multifocal Warthin’s Tumor: An Uncommon Presentation of Bilateral Cervical Lymphadenopathy - Ryan A. Rimmer; Elizabeth E. Cottrill (Case Reports in Otolaryngology)
Warthin’s tumor is the second most common benign lesion of the parotid gland. It is most commonly encountered in male smokers in the fifth to seventh decades of life. Uniquely, among benign lesions of the parotid gland, it can be seen bilaterally in 7–10% of cases. Very rarely, Warthin’s tumor can also mimic malignant or metastatic disease by presenting within cervical lymph nodes. We present a rare case of a 71-year old male smoker with bilateral parotid lesions in addition to progressively enlarging cervical and mediastinal lymphadenopathy. Excisional biopsy of a cervical lymph node ultimately revealed Warthin’s tumor.